Interdecadal Change in the Relationship Between the Bay of Bengal Summer Monsoon and South China Sea Summer Monsoon Onset - Zeng, Zhenjie; Guo, Yuanyuan; Wen, Zhiping (Frontiers in Earth Science, 2021)
The interdecadal change of the BOBSM-SCSSM relationship around the late 1970s is investigated in this paper. As we found that the correlation between BOBSM and SCSSM is 0.22 in 1958–1979, while it is 0.66 in 1980–2018. Further analyses showed that the strength of SAH at upper-troposphere circulation experiences an interdecadal enhancement around the late 1970s, meanwhile its meridional shift exhibits a wider range in second subperiod. Both the interdecadal change of the strength and meridional shift of SAH contribute to a closer relationship of BOBSM and SCSSM through modulating the divergent field at upper-troposphere. As for the external forcing, the basin-warming of Indian Ocean after the late 1970s may serves as a relatively primary factor, which could induce a consistent background flow that may favor a closer BOBSM-SCSSM relationship in the second period. It is noted that the Indian Ocean warming is related to high pressure anomaly widely lying to the south of 20°N at upper-troposphere, accompanied by the low pressure anomaly center to the north of 20°N. And this kind of upper-level circulation may result in strong westerly anomaly at the domain where the pressure gradient is large and then modulate the onset of BOBSM and SCSSM in 1980–2018 through changing the upper-level divergent field. Besides, the low-troposphere circulation associated with Indian Ocean warming is featured by the zonal-elongated high pressure anomaly spanning from the BOB, SCS to the northwest Pacific. The above coupling of the upper- and lower-troposphere, as a larger-scale consistent background flow controls the BOB and SCS, can modulate the interannual variation of BOBSM and SCSSM synchronously and contributes to closer relationship of BOBSM and SCSSM in the second subperiod.